Insights into wood species and aging effects on pyrolysis characteristics and combustion model by multi kinetics methods and model constructions. (April 2023) - Liu, Hao; Li, Mi; Zhao, Shuna; Mensah, Rhoda Afriyie; Das, Oisik; Jiang, Lin; Xu, Qiang
Abstract: Considering the extensive application of wood materials in the construction and manufacturing, waste wood has potential of converting into new natural energy sources. In this study, cypress, pine and fir woods commonly used in China, as well as old samples for above each species (more than 200 years old) have been used to study the aging and species effects on their thermal stability and combustion models. To obtain the kinetic triplets of the pyrolysis process, all samples have been heated in a nitrogen atmosphere with heating rates of 5, 10, 15, and 20 K min −1 . The kinetics parameters of pyrolysis throughout the conversion process were then calculated using isoconversional method, Coats-Redfern (CR), and masterplots methods. The reconstructed theoretical models have been then adjusted using the accommodation functions. The results of this study contribute to an increased understanding of the fire mechanism of waste woods, and implications concerning to provide scientific theoretical guidance for its feasibility as a new energy fuel more efficiently.